Influence of electrolites, ionic species and exchangeable sodium on soil dispersion. - Otero-Gómez, Lázara María (2012)
The objetive of this work was to determine the dispersing effect of salinity in a Gleysol petrogleyic soil of Artemisa, Pinardel Río, Cuba cropped with rice. The dispersing effect was determined from multiple lineal regresions obtained from the dispersion coefficient of the soils with the exchangeable sodiun percentage (PSI), electric conductivity (EC) andionic strengh that provide the total and free ions duringthe years 1997 to 2001, to discern the contribution of thesalinity indicators % Na+ (PSI), total ionic strength (It),free ionic strength (Il), electrical conductivity, and othersun-considered factors to the dispersion of the soils. High average dispersion of these soils masked the effect of electrolite accumulation, counteracting it, with exchangeable sodium showing dispersing effect in electric conductivityranges of 2,01 - 4 dS.m-1 and aNa+.(aCa2+)-0,5 total 5,01 - 7(mmol.L-1)0,5.